Implementasi Permensos Nomor 8 Tahun 2021 Tentang Penyelenggaraan Pengumpulan Uang atau Barang dalam Praktek Pengumpulan Donasi Bencana Alam oleh Mahasiwa - Ratih Sulastri; Zamroni Abdussamad; Fitran Amrain (Lembaga Pengembangan Kinerja Dosen, 2026)
Collecting donations for natural disaster victims is a form of social solidarity widely practiced by the community, including students. However, in practice, these fundraising activities must be carried out in accordance with applicable legal provisions, specifically Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 8 of 2021 concerning the Implementation of the Collection of Money or Goods (PUB). This study aims to analyze the implementation of Ministerial Regulation Number 8 of 2021 in the practice of collecting donations for natural disasters by students. The research method used is a normative empirical research method with a legislative and sociological approach. Data were obtained through literature review and interviews with the Social Services Agency and student organizations. The results show that the implementation of Ministerial Regulation Number 8 of 2021 in student fundraising activities has actually taken place, but is not yet fully optimal. This is evident in the continued discovery of donation collections carried out without official permits from authorized agencies and the lack of accountability reporting for collected funds. This condition indicates that the level of compliance with administrative provisions in the implementation of fundraising is still relatively low. Therefore, increased regulatory dissemination, more effective oversight, and increased legal awareness among students are needed to ensure that fundraising activities are carried out transparently, accountably, and in accordance with applicable laws.